The Influence Of Big Five Personality On Customer Satisfaction With Interpersonal Relationship Quality As A Mediating Variable Among Cooperative Facilitators In The West Kalimantan Province - Mahdi, Irfan; Ahmadia, Eru (Inovbook Publications, 2024)
The purpose of this study is to analyze the impact of Big Five Personality traits on customer satisfaction, with the quality of interpersonal relationships serving as a mediating variable among cooperative facilitators in West Kalimantan Province. This quantitative study utilized questionnaires for data collection and Structural Equation Modeling (SEM) with Smart PLS software for data analysis. It involved 41 cooperative assistants and 41 targeted cooperatives in West Kalimantan. Employing total sampling, the study aimed to analyze the impact of the Big Five Personality traits on customer satisfaction, with interpersonal relationship quality as a mediating variable among cooperative assistants in West Kalimantan. This study discovered that the quality of interpersonal relationships has a significant positive correlation with customer satisfaction, with personality dimensions such as Extraversion, Agreeableness, and Conscientiousness contributing positively. Although Openness to Experiences and Neuroticism did not demonstrate statistically significant relationships, this research underscores the importance of understanding the role of interpersonal relationship quality in the context of personality traits to enhance customer satisfaction. This study has significant limitations, including a sample size confined to cooperative assistants in West Kalimantan, reliance on quantitative methods with questionnaires, and the use of Smart PLS statistical software in SEM analysis. Other limitations encompass the potential influence of external factors not captured in the study and constraints in generalizing the results to other contexts. The research outcomes have tangible implications for business. Decision-makers can utilize these insights to enhance strategies and training initiatives, ultimately fostering positive customer experiences. This study examines the Big Five Personality traits. Consumer satisfaction is determined by the extent to which the benefits of a product or service align with consumer expectations. Interpersonal relationship quality mediates the relationship between Big Five Personality traits and consumer satisfaction.